Seasonal variation in the nutrient profile of Arthrospira fusiformis biomass harvested from an Ethiopian soda lake, Lake Chitu - Assaye, Hirut; Belay, Amha; Desse, Gulelat; Gray, David (Springer, 2017)
The extent of seasonal variation in the nutrient profile of Arthrospira biomass harvested from Lake Chitu was investigated to evaluate the variability of the quality of the product over a period of a year. Protein content varied from 47.9 to 55.7% for wet season biomass samples and from 39.2 to 40.8% for dry season samples. Dry season samples were characterized by relatively higher carbohydrate values (38.0–41.3%). Higher proportion of amino acids and unsaturated fatty acids were recorded for biomass harvested in wet season. Similarly, higher contents of phytonutrients (pigments) were recorded for wet season biomass samples: chlorophyll a (8.2–10.3 mg g−1), phycobiliproteins (104.1–120.7 mg g−1), total carotenoids (3.17–4.31 mg g−1), and β-carotene (1.24–1.61 mg g−1). The contents of Na and K were higher for a dry season biomass whereas other major (Ca, P, Mg) and trace (Mn, Fe, Cu, Zn, Se) minerals were found relatively in higher quantities in a wet season biomass. The nutritional composition of Arthrospira from Lake Chitu was found to be relatively comparable to that found in commercial Arthrospira products in the market. The significance of the findings is discussed in relation to potential sustainable production of Arthrospira biomass from this lake.